Clinical Significance of Dashavidha Pariksha in Diagnosis (AYUSHDHARA, 2025)
Ayurveda, the ancient Indian medical science, emphasizes a holistic and individualized approach to diagnosis and treatment. One of its foundational principles, “Rogamadou Pareekshet Tathonantaram Aoushadam,” underscores the necessity of thorough examination before initiating therapy. Dashavidha Pariksha, or the tenfold examination, is a comprehensive clinical assessment method designed to evaluate both the disease (Roga) and the patient (Rogi).The ten parameters include: Prakriti (constitution), Vikriti (current pathological state), Sara (quality of dhatus), Samhanana (compactness of the body), Pramana (body or organs measurements), Satmya (dietary and environmental compatibility), Satva (psychological strength), Ahara shakti (digestive capacity), Vyayama shakti (exercise tolerance), and Vaya (age). These parameters help assess the patient’s physical and mental strength, disease prognosis, and suitability for specific treatments.Among these, Vikriti Pariksha aids in identifying the disease process, while the other nine parameters offer insights into the patient's overall condition and vitality. This comprehensive analysis supports accurate diagnosis, individualized treatment planning, and better clinical outcomes.The clinical significance of Dashavidha Pariksha lies in its integrative perspective that combines physiological, psychological, and lifestyle-related factors. It empowers the physician to understand the unique constitution and strength of each patient, promoting personalized and precise healthcare. This article explores the relevance of each component of Dashavidha Pariksha in current Ayurvedic practice and highlights its enduring importance in effective clinical decision-making.